Status of agroforestry systems in South Saurashtra- Gujarat - Tandel, Minalkumar Bhagvanbhai; Sanjana J. Vaghasiya; M R Parmar; S M Patel; Jahanvi D. Chauhan (Indian Journal of Agroforestry, 2025)
The present survey work was carried out in four selected districts (Amreli, Bhavnagar, Gir Somnath and Junagadh) of South Saurashtra region of Gujarat State. An ex – post facto research design was used. The respondents, villages, talukas of districts were purposively selected through multi-stage sampling. From each district two talukas were selected; from each taluka, two villages were selected and from each village two respondents were selected for this survey work. In this way 64 respondents were collected from 32 villages of 16 talukas of 4 districts. The interview schedule of responses was prepared for survey work. Total 64 respondents were selected. In South Saurashtra region of Gujarat, 4 major agroforestry systems (Agrisilvicultural systems, Agrosilvopastoral systems, Agroforestry woodlots and Horticulture based agroforestry systems) along with 10 agroforestry sub-systems were identified. Two different types of woody components i.e., forest trees and fruit trees and five different non-woody components viz., food crop, fodder crop / pasture, cash crops, vegetables and fruit crop were reported under agroforestry systems in South Saurashtra (Gujarat). The functional unit of woody components consist of 5 different types of trees (Teak, Eucalyptus, Sandalwood, Melia and Casuarina) along with 13 different types of fruit trees (Mango, Citrus, Khirni, Guava, Custard apple, Jamun, Coconut, Cashew nut, Sapota, Tamarind, Drum stick, Ber and Pomegranate). Whereas, the functional unit of non- woody components consists of 8 different type of food crops (Maize, Groundnut, Wheat, Sesame, Soyabean, Coriander, Pearl millet and Chick pea); 4 types of cash crops (Groundnut, Sugarcane, Cotton and Chili); 1 type of fodder crops / pasture; 4 different types of vegetables (Onion, Tomato, Cabbage and Cauliflower) and 1 fruit crop (Papaya).